At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

2,-2,-6,-10,-14, ...how do I go about finding the explicit formula?

Sagot :

According to the given sequence, the difference is -4, because it's decreasing with that difference: 2-2 = -2; -2-4 = -6; and so on.

To find the explicit formula, we use the arithmetic sequence formula.

[tex]a_n=a_1+(n-1)d[/tex]

Replacing all the given information, we have.

[tex]\begin{gathered} a_n=2+(n-1)\cdot(-4) \\ a_n=2-4n+4 \\ a_n=6-4n \end{gathered}[/tex]

This explicit formula we can also express as

[tex]f(n)=6-4n[/tex]